PENGARUH KOMUNIKASI ORGANISASI DAN MOTIVASI TERHADAP PENGEMBANGAN KARIR GURU SMP/SEDERAJAT DI RAYON I PEMERINTAH KABUPATEN KARIMUN - Debby Sylvia Astuti (Universitas Negeri Jakarta, 2014)
The objective of this research is to understand comprehensively the effect of organizational communication and motivation on the career development of the junior high school or the same level’s teacher in Zone I of Karimun’s Government Regency. Research based of junior high school or the same level’s government teacher with total sample 156 teachers with simple random sampling. The data were collected through participants observation using survey by questionnaire. The data analysis and interpretation indicates that (1) organizational communication has positive influence on career development, (2) motivation has positive influence on career development, (3) organizational communication has positive influence on motivation. Result of the the research give information that an organization, in this case in Karimun’s Government Regency, the teachers can get the best career development by increase organizational communication and have a high motivation.